Experience with ceftazidime-avibactam treatment in a tertiary care center in Saudi Arabia - Abdullah Algwizani; Mohammad Alzunitan; Ahmad Alharbi; Abdulrahman Alsaedy; Sameera Aljohani; Bassam Alalwan; Jawaher Gramish; Adel Alothman (Elsevier, 2018)
Introduction: Carbapenem-resistant organisms have become major healthcare-associated pathogens and are responsible for significant morbidity and mortality worldwide. Cases and managements: This case-series describes our experience with ceftazidime-avibactam in the treatment of six cases with carbapenem-resistant organisms in King Abdulaziz Medical City in Riyadh, Saudi Arabia. After trying various combinations of antibiotic therapies without improvement, cases were treated with ceftazidime-avibactam. Outcomes: Five of the six achieved complete cure, both clinically and microbiologically. Keywords: MDR-infections, Ceftazidime-avibactam, Saudi Arabia